Carbon aerogel loaded with self-assembly of nano-silver particles and preparation method and use thereof
By self-assembling nanosilver particles in the carbon aerogel framework to form a SERS substrate with high stability and mechanical properties, the problems of poor chemical stability and mechanical properties of SERS substrate materials in the prior art are solved, and the ability to efficiently detect trace organic matter is achieved.
Patent Information
- Application Number
- CN202210472693.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-04-29
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-04-29
AI Technical Summary
Existing SERS substrate materials such as silica or their composite aerogels have problems of poor chemical stability and poor mechanical properties, which are difficult to meet the needs of efficient detection.
The carbon aerogel with self-assembly loaded nanosilver particles was used as the SERS substrate, and the carbon aerogel was soaked in a mixed solution of polyvinylpyrrolidone K90, ethylene glycol and silver nitrate, and the silver nitrate was reduced under constant temperature oil bath to form self-assembly silver nanoparticles loaded in the carbon aerogel framework.
It has achieved high chemical stability and mechanical properties, has good adsorption and detection capabilities, and can detect trace amounts of organic molecules such as 4-ATP in real time and quickly.
Smart Images

Figure CN114894770B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of SERS substrate preparation, and in particular to a carbon aerogel loaded with self-assembly of nano silver particles and a preparation method thereof and use thereof as a SERS substrate. Background Art
[0002] Surface enhanced Raman scattering (SERS) can realize real-time rapid detection of persistent organic pollutants (POPS). Different from the conventional chromatography / mass spectrometry method, which has the problems of complex pre-treatment process and difficulty in rapid detection, SERS detection has the advantages of high sensitivity, fingerprint characteristics, good repeatability, and short cycle. Aerogel has strong adsorption due to its ultra-large porosity and specific surface area, and is a good SERS substrate skeleton. However, in the prior art, using silica or its composite aerogel as the SERS substrate skeleton has problems such as poor chemical stability and poor mechanical properties. Summary of the invention
[0003] One of the purposes of the present invention is to provide a method for preparing carbon aerogel loaded with self-assembly of nano-silver particles, so as to overcome the disadvantage of poor mechanical properties existing in the preparation method in the prior art.
[0004] To achieve the above object, the present invention adopts the following technical solutions:
[0005] A method for preparing a carbon aerogel loaded with self-assembled nano-silver particles comprises the following steps:
[0006] Step S1, adding polyvinyl pyrrolidone K90 to ethylene glycol, and then adding silver nitrate to obtain a mixed solution;
[0007] Step S2, immersing the carbon aerogel in the above mixed solution for 12 to 24 hours, and oil bathing at a constant temperature of 120 to 180° C. for 0.5 to 2 hours to obtain the carbon aerogel loaded with self-assembled nano-silver particles coated with polyvinyl pyrrolidone K90, washing with alcohol to remove the polyvinyl pyrrolidone K90 at a constant temperature, and drying at room temperature to obtain the carbon aerogel loaded with self-assembled nano-silver particles.
[0008] As a further improvement of the preparation method of the above-mentioned nanosilver particle self-assembled carbon aerogel:
[0009] Preferably, in step S1, the concentration of polyvinyl pyrrolidone K90 in the mixed solution is 10-35 mg / ml, and the concentration of silver nitrate in the mixed solution is 25-100 mol / L
[0010] Preferably, the preparation method of the carbon aerogel is as follows:
[0011] Step A, mixing carbon nanotubes, deionized water and sodium dodecyl sulfate, and stirring at room temperature to completely disperse the carbon nanotubes to prepare a carbon nanotube dispersion;
[0012] Step B, adding resorcinol, formaldehyde and sodium carbonate to the carbon nanotube dispersion, stirring at room temperature to completely dissolve the resorcinol and formaldehyde in the carbon nanotube dispersion, and then slowly dropping epichlorohydrin under stirring to obtain a carbon aerogel precursor sol;
[0013] Step C, sealing the carbon aerogel precursor sol to fully gelate it to obtain a carbon aerogel precursor gel;
[0014] Step D, replacing the carbon aerogel precursor gel with tert-butyl alcohol, and then freeze-drying it to obtain a phenolic-wrapped carbon nanotube aerogel;
[0015] Step E: calcining the carbon nanotube aerogel wrapped with phenolic aldehyde at high temperature and then slicing it to obtain the carbon aerogel.
[0016] As a further improvement of the preparation method of carbon aerogel:
[0017] Preferably, in step A, the added amounts of carbon nanotubes and sodium dodecyl sulfate are 1-10 wt% and 5-10 wt% of the total mass of the carbon nanotube dispersion, respectively.
[0018] Preferably, in step B, the molar ratio of resorcinol to formaldehyde is 1:2, the concentration of resorcinol in the mixed solution is 0.1-0.5 mol / L, the concentration of formaldehyde in the mixed solution is 0.2-1 mol / L, the concentration of sodium carbonate in the mixed solution is 0.2-1 mmol / L, and the amount of epichlorohydrin added is 1-5% of the total volume of the carbon aerogel precursor sol.
[0019] Preferably, in step C, the carbon aerogel precursor sol is placed at a temperature of 50 to 180° C. for 5 to 48 hours to fully gelate it.
[0020] Preferably, in step D, the replaced carbon aerogel precursor gel is placed at a temperature of -80 to -10°C for 10 to 36 hours for freeze drying.
[0021] Preferably, the specific steps of the high-temperature calcination in step E are as follows: using high-purity nitrogen with a N2 content of more than 99.999% as a protective gas, placing the phenolic carbon nanotube aerogel in a high-temperature tubular furnace, heating from room temperature to 500°C at a rate of 1 to 5°C / min, then heating to 700 to 1000°C at a rate of 2 to 8°C / min, and keeping at this temperature for 60 to 180 minutes, and finally cooling naturally to room temperature.
[0022] The second object of the invention is to provide a carbon aerogel loaded with self-assembled nano-silver particles prepared by any of the above preparation methods.
[0023] The third object of the present invention is to provide a use of the above-mentioned carbon aerogel loaded with self-assembled nano-silver particles as a three-dimensional flexible SERS substrate.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1) The method for preparing carbon aerogel with the aid of a crosslinker provided by the present invention adopts a sol-gel method, and uses resorcinol, formaldehyde, carbon nanotubes, sodium carbonate, and epichlorohydrin as raw materials to form a sol in an aqueous system. After gelation, the solvent is fully replaced with tert-butyl alcohol and dried, and then calcined at high temperature under a nitrogen atmosphere to obtain a carbon aerogel. The carbon aerogel is immersed in a mixed solution of ethylene glycol, silver nitrate, and polyvinyl pyrrolidone, and the silver nitrate is reduced in an ethylene glycol oil bath to obtain self-assembled silver nanoparticles loaded in the carbon aerogel skeleton, and the polyvinyl pyrrolidone on the surface of the nanosilver particles is further removed by alcohol washing, thereby obtaining a carbon aerogel loaded with self-assembled silver nanoparticles as a three-dimensional flexible SERS substrate. Realize real-time rapid detection of trace amounts of 4-ATP.
[0026] 2) The preparation method only requires common laboratory equipment, no special equipment, and no special drugs. The process is simple and easy to operate, the reaction process is easy to control, the production cycle is short, the cost is low, and mass production is possible.
[0027] 3) The self-assembled silver nanoparticles of the present invention are loaded on the carbon aerogel with certain adsorption. Due to the porous structure and large specific surface area of the carbon aerogel, strong adsorption is achieved that is favorable to the target molecules, thereby enabling the molecules to be tested adsorbed on the surface of the silver nanoparticles to achieve surface enhanced Raman scattering; secondly, the carbon material has good chemical stability and thermal stability, and the carbon aerogel constructed by carbon nanotubes with a large aspect ratio can achieve rebound after compression, which improves its mechanical properties to a certain extent. Trace and rapid detection of reagents such as 4-ATP can be achieved. The self-assembled silver nanoparticle-loaded carbon aerogel prepared by the method has a surface enhanced Raman effect. As a three-dimensional flexible SERS substrate, it has good flexibility, adsorption and good detection ability, can detect two organic molecules at the same time, and detect trace 4-ATP in real time and quickly. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0029] Figure 1 The scanning electron microscope photographs are obtained by using a scanning electron microscope to perform morphological detection on the three-dimensional flexible SERS substrates prepared in Examples 1 to 4 of the present invention and Comparative Example 1 at a magnification of 10k.
[0030] Figure 2 These are optical photographs of the three-dimensional flexible SERS substrate prepared in Example 3 before and after bending transformation.
[0031] Figure 3 These are Raman comparison graphs of SERS performance detection of the three-dimensional flexible SERS substrate prepared in Examples 1 to 4 and Comparative Example 1, and Raman graphs of detection of different concentrations of trace 4-ATP in the comparative example. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention.
[0033] In order to more clearly demonstrate the technical solution and technical effects provided by the present invention, the method for preparing carbon aerogel with the assistance of a cross-linking agent provided by an embodiment of the present invention is described in detail with reference to specific embodiments.
[0034] Example 1
[0035] A method for preparing a three-dimensional flexible SERS substrate comprises the following steps:
[0036] Step a1, weighing 0.5 ml of carbon nanotubes and 25 mg of sodium dodecyl sulfate, putting them into the same reaction kettle and mixing them, then pouring 8.7 ml of deionized water into the kettle, and using a magnetic stirrer to stir the mixture at a constant temperature at room temperature until the carbon nanotubes are completely dissolved in the deionized water, thereby obtaining a carbon nanotube dispersion with good dispersibility;
[0037] Step b1, adding 0.44 g of resorcinol, 0.6 ml of formaldehyde (analytical grade), and 0.4 ml (concentration 2 mg / ml) of sodium carbonate solution to the solution, stirring continuously at room temperature, and then slowly dropping 1.72 ml of epichlorohydrin to obtain a carbon aerogel precursor sol;
[0038] Step c1, sealing the precursor sol, and placing it in a constant temperature box at 100° C. for 12 hours to fully gelate it, thereby obtaining a carbon aerogel precursor gel;
[0039] Step d1, subjecting the carbon aerogel precursor gel to solvent replacement, and then placing it in a freeze dryer and drying it at -50°C for 24 hours to completely dry it, thereby obtaining a phenolic-wrapped carbon nanotube aerogel;
[0040] Step e1, putting the phenolic-wrapped carbon nanotube aerogel into a graphite crucible, placing it in a high-temperature tube furnace, using high-purity nitrogen (N2≥99.999%) as a protective gas, heating from room temperature to 500°C at a rate of 2°C / min, then heating to 800°C at a rate of 5°C / min, and keeping the temperature for 120min, and finally cooling naturally to room temperature, thereby obtaining a carbon aerogel block, and slicing it into carbon aerogel for standby use;
[0041] Step f1, immersing the carbon aerogel in a mixed solution of 25 ml ethylene glycol and 0.6 g polyvinyl pyrrolidone (K90), adding 0.11 g silver nitrate, the concentration of silver nitrate in the solution is 25 mM, sealing for 18 hours, and oil bathing for 1 hour at a constant temperature of 160° C. to fully reduce the silver nitrate and load it in the carbon aerogel network skeleton, thereby obtaining a carbon aerogel coated with polyvinyl pyrrolidone and loaded with self-assembled nanosilver particles.
[0042] Step g1, washing the carbon aerogel loaded with self-assembled nano-silver particles coated with polyvinyl pyrrolidone with alcohol at a constant temperature of 60° C. for 6 hours, and drying at room temperature.
[0043] Example 2
[0044] A method for preparing a three-dimensional flexible SERS substrate may include the following steps:
[0045] Step a1, weigh 0.5 ml of carbon nanotubes and 25 mg of sodium dodecyl sulfate, put them into the same reactor and mix them, then pour 8.7 mL of deionized water into it, and use a magnetic stirrer to stir it at a constant temperature at room temperature until the carbon nanotubes are completely dissolved in the deionized water, thereby obtaining a carbon nanotube dispersion with good dispersibility.
[0046] Step b1, add 0.44g of resorcinol, 0.6ml of formaldehyde (analytical grade), and 0.4ml (concentration 2mg / ml) of sodium carbonate solution to the solution, continue stirring at room temperature, and then slowly drop 1.72mL of epichlorohydrin to obtain a carbon aerogel precursor sol.
[0047] Step c1, sealing the precursor sol, and placing it in a constant temperature box at a constant temperature of 100° C. for 12 hours to fully gelate it, thereby obtaining a carbon aerogel precursor gel.
[0048] Step d1, subjecting the carbon aerogel precursor gel to solvent replacement, and then placing it in a freeze dryer and drying it at -50°C for 24 hours to completely dry it, thereby obtaining a carbon aerogel precursor xerogel.
[0049] Step e1, the precursor dry gel is loaded into a graphite crucible, placed in a high-temperature tube furnace, and high-purity nitrogen (N2≥99.999%) is used as a protective gas. The temperature is raised from room temperature to 500°C at a rate of 2°C / min, and then raised to 800°C at a rate of 5°C / min, and kept warm for 120 minutes, and finally naturally cooled to room temperature, thereby obtaining a carbon aerogel block.
[0050] Step f1, immersing the carbon aerogel slice in a mixed solution of 25 ml ethylene glycol and 0.6 g polyvinyl pyrrolidone (K90), adding 0.21 g silver nitrate, the concentration of silver nitrate in the solution is 50 mM, sealing for 18 hours, and oil bathing for 1 hour at a constant temperature of 160° C. to fully reduce the silver nitrate and load it in the carbon aerogel network skeleton, thereby obtaining a carbon aerogel loaded with self-assembled nanosilver particles coated with polyvinyl pyrrolidone.
[0051] Step g1, washing the carbon aerogel loaded with self-assembled nano-silver particles coated with polyvinyl pyrrolidone with alcohol at a constant temperature of 60° C. for 6 hours, and drying at room temperature.
[0052] Example 3
[0053] A method for preparing a three-dimensional flexible SERS substrate comprises the following steps:
[0054] Step a1, weigh 0.5 ml of carbon nanotubes and 25 mg of sodium dodecyl sulfate, put them into the same reactor and mix them, then pour 8.7 mL of deionized water into it, and use a magnetic stirrer to stir it at a constant temperature at room temperature until the carbon nanotubes are completely dissolved in the deionized water, thereby obtaining a carbon nanotube dispersion with good dispersibility.
[0055] Step b1, add 0.44g of resorcinol, 0.6ml of formaldehyde (analytical grade), and 0.4ml (concentration 2mg / ml) of sodium carbonate solution to the solution, continue stirring at room temperature, and then slowly drop 1.72mL of epichlorohydrin to obtain a carbon aerogel precursor sol.
[0056] Step c1, sealing the precursor sol, and placing it in a constant temperature box at a constant temperature of 100° C. for 12 hours to fully gelate it, thereby obtaining a carbon aerogel precursor gel.
[0057] Step d1, subjecting the carbon aerogel precursor gel to solvent replacement, and then placing it in a freeze dryer and drying it at -50°C for 24 hours to completely dry it, thereby obtaining a phenolic-wrapped carbon nanotube aerogel.
[0058] Step e1, putting the phenolic-wrapped carbon nanotube aerogel into a graphite crucible, placing it in a high-temperature tube furnace, using high-purity nitrogen (N2≥99.999%) as a protective gas, heating from room temperature to 500°C at a rate of 2°C / min, then heating to 800°C at a rate of 5°C / min, and keeping the temperature for 120min, and finally cooling naturally to room temperature, thereby obtaining a carbon aerogel block, and slicing it into carbon aerogel for standby use;
[0059] Step f1, immersing the carbon aerogel in a mixed solution of 25 ml ethylene glycol and 0.6 g polyvinyl pyrrolidone (K90), adding 0.32 g silver nitrate, the concentration of silver nitrate in the solution is 75 mM, sealing for 18 hours, and oil bathing for 1 hour at a constant temperature of 160° C. to fully reduce the silver nitrate and load it in the carbon aerogel network skeleton, thereby obtaining a carbon aerogel coated with polyvinyl pyrrolidone and loaded with self-assembled nanosilver particles.
[0060] Step g1, washing the carbon aerogel loaded with self-assembled nano-silver particles coated with polyvinyl pyrrolidone with alcohol at a constant temperature of 60° C. for 6 hours, and drying at room temperature.
[0061] Example 4
[0062] A method for preparing a three-dimensional flexible SERS substrate comprises the following steps:
[0063] Step a1, weigh 0.5 ml of carbon nanotubes and 25 mg of sodium dodecyl sulfate, put them into the same reactor and mix them, then pour 8.7 mL of deionized water into it, and use a magnetic stirrer to stir it at a constant temperature at room temperature until the carbon nanotubes are completely dissolved in the deionized water, thereby obtaining a carbon nanotube dispersion with good dispersibility.
[0064] Step b1, add 0.44g of resorcinol, 0.6ml of formaldehyde (analytical grade), and 0.4ml (concentration 2mg / ml) of sodium carbonate solution to the solution, continue stirring at room temperature, and then slowly drop 1.72mL of epichlorohydrin to obtain a carbon aerogel precursor sol.
[0065] Step c1, sealing the precursor sol, and placing it in a constant temperature box at a constant temperature of 100° C. for 12 hours to fully gelate it, thereby obtaining a carbon aerogel precursor gel.
[0066] Step d1, subjecting the carbon aerogel precursor gel to solvent replacement, and then placing it in a freeze dryer and drying it at -50°C for 24 hours to completely dry it, thereby obtaining a phenolic-wrapped carbon nanotube aerogel.
[0067] Step e1, putting the phenolic-wrapped carbon nanotube aerogel into a graphite crucible, placing it in a high-temperature tube furnace, using high-purity nitrogen (N2≥99.999%) as a protective gas, heating from room temperature to 500°C at a rate of 2°C / min, then heating to 800°C at a rate of 5°C / min, and keeping the temperature for 120min, and finally cooling naturally to room temperature, thereby obtaining a carbon aerogel block, and slicing it into carbon aerogel for standby use;
[0068] Step f1, immersing the carbon aerogel in a mixed solution of 25 ml ethylene glycol and 0.6 g polyvinyl pyrrolidone (K90), adding 0.43 g silver nitrate, the concentration of silver nitrate in the solution is 100 mM, sealing for 18 hours, and oil bathing for 1 hour at a constant temperature of 160° C. to fully reduce the silver nitrate and load it in the carbon aerogel network skeleton, thereby obtaining a carbon aerogel coated with polyvinyl pyrrolidone and loaded with self-assembled nanosilver particles.
[0069] Step g1, washing the carbon aerogel loaded with self-assembled nano-silver particles coated with polyvinyl pyrrolidone with alcohol at a constant temperature of 60° C. for 6 hours, and drying at room temperature.
[0070] Comparative Example 1
[0071] A method for preparing a three-dimensional flexible SERS substrate comprises the following steps:
[0072] Step a1, weigh 0.5 ml of carbon nanotubes and 25 mg of sodium dodecyl sulfate, put them into the same reactor and mix them, then pour 8.7 ml of deionized water into it, and use a magnetic stirrer to stir it at a constant temperature at room temperature until the carbon nanotubes are completely dissolved in the deionized water, thereby obtaining a carbon nanotube dispersion with good dispersibility.
[0073] Step b1, add 0.44g of resorcinol, 0.6ml of formaldehyde (analytical grade), and 0.4ml (concentration 2mg / ml) of sodium carbonate solution to the solution, continue stirring at room temperature, and then slowly drop 1.72ml of epichlorohydrin to obtain a carbon aerogel precursor sol.
[0074] Step c1, sealing the precursor sol, and placing it in a constant temperature box at a constant temperature of 100° C. for 12 hours to fully gelate it, thereby obtaining a carbon aerogel precursor gel.
[0075] Step d1, subjecting the carbon aerogel precursor gel to solvent replacement, and then placing it in a freeze dryer and drying it at -50°C for 24 hours to completely dry it, thereby obtaining a phenolic-wrapped carbon nanotube aerogel.
[0076] Step e1, put the phenolic-wrapped carbon nanotube aerogel into a graphite crucible, put it into a high-temperature tube furnace, use high-purity nitrogen (N2≥99.999%) as a protective gas, heat it from room temperature to 500°C at a rate of 2°C / min, then heat it to 800°C at a rate of 5°C / min, and keep it warm for 120 minutes, and finally cool it naturally to room temperature to obtain a carbon aerogel block, which is sliced into carbon aerogel.
[0077] Morphology observation and performance testing
[0078] The morphology and performance of the three-dimensional flexible SERS substrates prepared in Examples 1 to 4 of the present invention and Comparative Example 1 were observed and tested, and the following results were obtained:
[0079] (1) The three-dimensional flexible SERS substrates prepared in Examples 1 to 4 of the present invention and Comparative Example 1 were tested by scanning electron microscopy to obtain the following: Figure 1 The scanning electron microscope photo shown. Figure 1 a is a FESEM photograph of the three-dimensional flexible SERS substrate prepared in Example 1 of the present invention at a magnification of 10k; Figure 1 b is a FESEM photograph of the three-dimensional flexible SERS substrate prepared in Example 2 of the present invention at a magnification of 10k; Figure 1 c is a FESEM photograph of the three-dimensional flexible SERS substrate prepared in Example 3 of the present invention at a magnification of 10k; Figure 1 d is a FESEM photograph of the three-dimensional flexible SERS substrate prepared in Example 4 of the present invention at a magnification of 10k; Figure 1 e is a FESEM photograph of the substrate prepared in comparative example 1 of the present invention at a magnification of 10k. Examples 1 to 4 are respectively the cases where the concentration of silver nitrate is 25mM, 50mM, 75mM, and 100mM, and the comparative example is the case where no silver nitrate is added. Figure 1 It can be seen that as the concentration of silver nitrate increases, the number of silver nanoparticles increases greatly, and the particle size of silver nanoparticles increases. When the concentration of silver nitrate reaches 100mM, the boundaries of silver particles are blurred, and a silver film is loaded on the surface of the skeleton. Among them, the loading concentration of Example 3 is the best for the detection performance requirements; Comparative Example 1 has no detection capability.
[0080] (2) An optical camera is used to photograph the bending state of the three-dimensional flexible SERS substrate prepared in Example 3, thereby obtaining the following: Figure 2 Optical photograph shown. Figure 2It can be seen that the three-dimensional flexible SERS substrate prepared in Example 3 of the present invention has good bendability.
[0081] (4) The SERS spectra were collected using a confocal Raman system with an excitation wavelength of 532 nm, thereby obtaining the following Figure 3 Raman spectrum shown. Figure 3 a is the three-dimensional flexible SERS substrate prepared in Examples 1 to 4 of the present invention and Comparative Example 1 for a concentration of 10 -8 Raman spectrum of trace detection of 4-ATP reagent of M; Figure 3 b is the Raman spectrum of the three-dimensional flexible SERS substrate prepared in Example 3 for 4-ATP trace detection with different concentration gradients. Figure 3 It can be seen that the three-dimensional flexible SERS substrate prepared in Example 3 of the present invention has a good ability to detect trace amounts of 4-ATP.
[0082] In summary, the embodiments of the present invention not only have a simple preparation process, an easy-to-control reaction process, a short production cycle, and low cost, but also the prepared three-dimensional flexible SERS substrate has good adsorption, high detection signal capability, and good bendability.
[0083] Those skilled in the art should understand that the above are only some specific embodiments of the present invention, rather than all embodiments. It should be noted that for those of ordinary skill in the art, many modifications and improvements can be made, and all modifications or improvements that do not exceed the scope of protection of the present invention should be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a carbon aerogel loaded with self-assembled nano-silver particles, characterized in that: The steps include: Step S1, adding polyvinyl pyrrolidone K90 to ethylene glycol, and then adding silver nitrate to obtain a mixed solution; Step S2, soaking the carbon aerogel in the mixed solution for 12 to 24 hours, and then placing the carbon aerogel in an oil bath at a constant temperature of 120 to 180° C. for 0.5 to 2 hours to obtain the carbon aerogel loaded with self-assembled nano-silver particles coated with polyvinyl pyrrolidone K90, washing the polyvinyl pyrrolidone K90 with alcohol at a constant temperature, and drying the carbon aerogel at room temperature to obtain the carbon aerogel loaded with self-assembled nano-silver particles; The preparation method of the carbon aerogel is as follows: Step A, mixing carbon nanotubes, deionized water and sodium dodecyl sulfate, and stirring at room temperature to completely disperse the carbon nanotubes to prepare a carbon nanotube dispersion; Step B, adding resorcinol, formaldehyde and sodium carbonate to the carbon nanotube dispersion, stirring at room temperature to completely dissolve the resorcinol and formaldehyde in the carbon nanotube dispersion, and then slowly dropping epichlorohydrin under stirring to obtain a carbon aerogel precursor sol; Step C, sealing the carbon aerogel precursor sol to fully gelate it to obtain a carbon aerogel precursor gel; Step D, replacing the carbon aerogel precursor gel with tert-butyl alcohol, and then freeze-drying it to obtain a phenolic-wrapped carbon nanotube aerogel; Step E: calcining the carbon nanotube aerogel wrapped with phenolic aldehyde at high temperature and then slicing it to obtain the carbon aerogel.
2. The method for preparing the carbon aerogel loaded with self-assembly of nano-silver particles according to claim 1, characterized in that: In step S1, the concentration of polyvinyl pyrrolidone K90 in the mixed solution is 10-35 mg / ml, and the concentration of silver nitrate in the mixed solution is 25-100 mol / L.
3. The method for preparing the carbon aerogel loaded with self-assembly of nano-silver particles according to claim 1, characterized in that: In step A, the addition amounts of carbon nanotubes and sodium dodecyl sulfate are 1-10 wt% and 5-10 wt% of the total mass of the carbon nanotube dispersion, respectively.
4. The method for preparing the carbon aerogel loaded with self-assembly of nano-silver particles according to claim 1, characterized in that: In step B, the molar ratio of resorcinol to formaldehyde is 1:2, the concentration of resorcinol in the mixed solution is 0.1-0.5 mol / L, the concentration of formaldehyde in the mixed solution is 0.2-1 mol / L, the concentration of sodium carbonate in the mixed solution is 0.2-1 mmol / L, and the amount of epichlorohydrin added is 1-5% of the total volume of the carbon aerogel precursor sol.
5. The method for preparing the carbon aerogel loaded with self-assembly of nano-silver particles according to claim 1, characterized in that: In step C, the carbon aerogel precursor sol is placed at a temperature of 50 to 180° C. for 5 to 48 hours to fully gelate it.
6. The method for preparing the carbon aerogel loaded with self-assembled nano-silver particles according to claim 1, characterized in that: In step D, the replaced carbon aerogel precursor gel is placed at a temperature of -80 to -10°C for 10 to 36 hours for freeze drying.
7. The method for preparing the carbon aerogel loaded with self-assembled nano-silver particles according to claim 1, characterized in that: The specific steps of high-temperature calcination in step E are as follows: using high-purity nitrogen with a N2 content of more than 99.999% as a protective gas, placing the phenolic carbon nanotube aerogel in a high-temperature tubular furnace, heating from room temperature to 500°C at a rate of 1 to 5°C / min, then heating to 700 to 1000°C at a rate of 2 to 8°C / min, and keeping at this temperature for 60 to 180 minutes, and finally cooling naturally to room temperature.
8. A carbon aerogel loaded with self-assembly of nano-silver particles prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the carbon aerogel loaded with self-assembled nanosilver particles as claimed in claim 8 as a three-dimensional flexible SERS substrate.
Citation Information
Patent Citations
Preparation method of novel high performance antibacterial nano-cellulose carbon aerogel
CN105053007A
Preparation method of super-hydrophobic high-absorption cellulose-based composite carbon aerogel with electromagnetic shielding effectiveness
CN110642590A